Melatonin attenuates hepatic oxidative stress by regulating the P62/LC3 autophagy pathway in PCOS - Junhui Zhang; Hongyan Zhang; Bao Guo; Jun Yang; Renxiang Yu; Wenxiu Chen; Muxin Zhai; Yuhan Cao; Yajing Liu; Qiang Hong; Fenfen Xie (Endocrine Connections)
The potential protective mechanisms of MT on hepatic OS in PCOS. MT could lead to a decrease in autophagy, presenting a decrease of LC3 and an increase of P62 in the PCOS liver. Increased P62 could reduce Nrf2 ubiquitination and increase its nuclear translocation and activation through direct interaction with Keap1. Thus, MT ultimately activated the Keap1-Nrf2 pathway, promoting nuclear Nrf2 expression to reduce hepatic OS. Abstract The elevated level of hepatic oxidative stress (OS) in polycystic ovary syndrome (PCOS) is one of the important causes of liver abnormalities. Therefore, decreasing the level of hepatic OS in PCOS is beneficial in reducing the risk of PCOS-related liver diseases. Melatonin (MT) is recognized as a potent antioxidant. Nevertheless, the efficacy of MT in alleviating hepatic OS associated with PCOS is yet to be established, and the precise mechanisms through which MT exerts its antioxidant effects remain to be fully elucidated. The aim of this study was to explore the potential mechanisms by which MT reduces hepatic OS in PCOS. First, we detected elevated OS levels in PCOS samples. Subsequently, with MT pretreatment, we discovered that MT could significantly diminish the levels of OS, liver triglycerides, total cholesterol, alanine aminotransferase, and aspartate aminotransferase, while concurrently ameliorating mitochondrial structural damage in the PCOS liver. Furthermore, we identified elevated autophagy levels in the liver of PCOS rats and an inhibition of the Keap1–Nrf2 pathway. Through MT pretreatment, the expression of LC3 was significantly decreased, while the Keap1–Nrf2 pathway was activated. Our study showed that MT could affect the Nrf2 pathway dependent on the P62/LC3 autophagy pathway, thereby attenuating hepatic OS in PCOS. These findings offer novel insights and research avenues for the study of PCOS-related liver diseases.